Pengaruh Voltase dan Stick Out terhadap Cacat Permukaan Las MIG Butt Joint Aluminium 6063 - Sulistyono, Sulistyono; Shafly Kh, Irfan Hariz (Jurnal Rekayasa Mesin, 2024)
Technological advances are currently experiencing a very rapid increase, one of which is bicycle transportation which is now popular, namely electric bicycles. In the assembly of the frame of an electric scooter, a welding process is needed, one of which is the MIG welding method. The purpose of this study is to determine the effect of welding voltage and stick out on weld defects from MIG welding results on aluminum 6063, the welding defects found are porosity, undercut, and incomplete fusion. According to the results of macro photo observations, the smaller the voltage, the less optimal the electrode melting, as well as the stick out which greatly affects the welding results, because the longer the  stick out, the more the voltage is inhibited, and the protective gas will be reduced due to the distance of the nozzle to the welding point is getting farther due to the longer stick out   distance